1991
DOI: 10.1007/bf00229983
|View full text |Cite
|
Sign up to set email alerts
|

Location of saccade-related neurons in the macaque superior colliculus

Abstract: The locations of saccade-related neurons were studied in the superior colliculi of two adult rhesus monkeys (Macaca mulatta) by placing marking lesions at the sites of physiologically characterized cells and comparing these histologically identified sites with the collicular laminae and acetylcholinesterase (AChE)-rich patches. Three major conclusions were drawn on the basis of 39 histologically identified sites at which saccade-related neurons were recorded. First, saccade-related neurons were distributed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…Previous work suggests that the brainstem cholinergic system modulates motor output via the projection from cholinergic PPTg neurons to the intermediate layers of the superior colliculus (SC; Beninato and Spencer 1986;Hall et al 1989;Ma et al 1991;Sooksawate and Isa 2006). Furthermore, motor-preparatory activity has been observed in the SC of several species (Dorris et al 1997;Glimcher and Sparks 1992;Harris 1980;Horwitz and Newsome 2001;Munoz et al 1991), including rodents performing a similar task to that used here Mainen 2008, 2012;Hirokawa et al 2011), with a comparable preponderance of preference for upcoming contralateral movements.…”
Section: Relationship With Activity In Other Sensorimotor Decision Rementioning
confidence: 68%
“…Previous work suggests that the brainstem cholinergic system modulates motor output via the projection from cholinergic PPTg neurons to the intermediate layers of the superior colliculus (SC; Beninato and Spencer 1986;Hall et al 1989;Ma et al 1991;Sooksawate and Isa 2006). Furthermore, motor-preparatory activity has been observed in the SC of several species (Dorris et al 1997;Glimcher and Sparks 1992;Harris 1980;Horwitz and Newsome 2001;Munoz et al 1991), including rodents performing a similar task to that used here Mainen 2008, 2012;Hirokawa et al 2011), with a comparable preponderance of preference for upcoming contralateral movements.…”
Section: Relationship With Activity In Other Sensorimotor Decision Rementioning
confidence: 68%
“…Kanaseki and Sprague 1974;Ma et al 1990Ma et al , 1991. Taking into account the details given by different studies and bearing in mind that the depth of the SC depends on laterality, we think it is reasonable to place this border at a maximal depth of 4 mm below the collicular surface.…”
Section: Discussionmentioning
confidence: 99%
“…In many reports orienting-related properties of collicular neurons have been described (for references see Schiller 1984;Sparks and Hartwich-Young 1989), and it is commonly accepted that the SC is mainly involved in the control of eye and head movements. Different populations of neurons seem to be "layered", as cells with visual properties are concentrated dorsally in the SC while saccadic and head-movement-related cells are more often found in the intermediate and ventral regions of the monkey SC (Cynader and Berman 1972;Ma et al 1991;Cowie and Robinson 1994). The latter authors could even elicit "movements of proximal limbs", usually from sites in the SC below those from which head movements could be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in rodents, cats, and primates have mapped the immunohistochemical profile and the afferent topography of the SC and have demonstrated that the cholinergic innervation of the superficial subdivision originates from the brain stem's parabigeminal nucleus (Feig et al 1992;Graybiel 1978;Hall et al 1989;Mufson et al 1986;RoldĂĄn et al 1983) whereas the deep subdivision innervation arises from the parabrachial region, primarily composed of the PPTg and the LDTg (Beninato and Spencer 1986;Graybiel 1978;Hall et al 1989;Harting and Van Lieshout 1991;Illing and Graybiel 1985;Jones and Webster 1988;Ma et al 1991;Stubblefield et al 2015;Wallace and Fredens 1988;Woolf and Butcher 1986). We focus on this latter innervation because the deep subdivision of the SC is directly involved in selecting targets for movements, although the superficial cholinergic input could in turn modulate intralaminar processing within the SC (Ghitani et al 2014;Isa et al 1998;Lee et al 1997).…”
Section: Cholinergic Input To Superior Colliculus From Parabrachial Rmentioning
confidence: 99%